A Survey on Offline Handwritten Text Recognition of Popular Indian Scripts - P, Sujatha; Lalitha Bhaskari, D (International Journal of Computer Sciences and Engineering, 2019)
Handwritten recognition is for all time a pioneering area of research in the field of pattern recognition and image processing and there is a huge demand for optical character recognition (OCR) on handwritten documents. Most of these systems work for Arabic, roman, Japanese and Chinese characters, but not as much of research on Indian languages, though there are 11 main scripts in India. This article provides a comprehensive survey of recent developments in popular Indian scripts for handwriting recognition by comparing the feature selection techniques, classifiers and the recognition accuracy for each technique. Finally, some future research directions on offline handwritten recognition techniques are discussed.